Anormalidad floral en Phytolacca icosandra L. (Phytolaccaceae) en el Pedregal de San Ángel, México, D.F. - Cruz Durán, Ramiro; Alcántara Ayala, Othón (Instituto de Ecología, A.C., 2000)
Cases of flower abnormalities are described in several individuals of Phytolacca icosandra L. that inhabit the Pedregal de San Angel, near the buildings of the Faculty of Sciences of the Universidad Nacional Autónoma de México, which previously harbored a scrub of Senecio praecox L. (“palo loco”) and now is in process of urbanization. The abnormalities consist mainly in the enlargement of the base of the ovary, which takes the appearance of a gynophore, as well as in the transformation of sepals, anthers and carpels into structures similar to leaves. In extreme cases a new branch emerges from the interior of the ovary.